Care, crisis and activism the politics of everyday life - Jupp, Eleanor ca. 20./21. Jh (Policy, 2022)
What kinds of care are being offered or withdrawn by the welfare state? What does this mean for the caring practices and interventions of local activists? Shedding new light on austerity and neoliberal welfare reform in the UK, this vital book considers local action and activism within contexts of crisis, including the COVID-19 pandemic
Title from publisher's bibliographic system (viewed on 19 Sep 2022)
Keywords: Social movements / Great Britain; Public welfare / Great Britain / Citizen participation; Medical care / Political aspects / Great Britain; Political participation / Great Britain; Wohlfahrtsstaat; Neoliberalismus; Sparpolitik; Aktivismus; Great Britain / Social conditions / 1945-; Großbritannien